SYNERGY OF MULTI-STAKEHOLDERS IN DEFENDING INDONESIA FROM CYBER THREATS - Rizki, Aththaariq; Timur, Fauzia Gustarina Cempaka (Journal of Social Political Sciences, 2021)
This paper argues that currently the threat of cyber-attacks has become a real threat that has the potential to develop in Indonesia. With the presence of these cyber-attacks, the government must take advantage of the synergy between state multi-stake holders to jointly face cyber threats that come to attack Indonesia. The purpose of this research is to answer the existing problem formulations, namely first to find out which state multi-stake holders are in synergy in defending cyber-attacks in Indonesia; and to analyze how the synergy of state multi-stake holders in dealing with cyber-attacks in Indonesia. The writing of this article was conducted using a qualitative method with a literature review approach that focuses on the synergy between state multi-stake holders in dealing with cyber-attacks in Indonesia. The theory used is the concept of synergy, state multi-stake holders, and the threat of cyber-attacks as a literature review. In this paper, the results show that the synergy concept consists of coordination; and communication, which is used by state multi-stake holders to face the threat of cyber-attacks. So that it can be concluded from this writing that state multi-stake holders who work together in defending cyber threats are: BSSN, Kominfo, Puskom Kemhan, Pusinfolahta TNI Headquarters, and Dittipidsiber Polri. In addition, the synergy of state multi-stake holders in dealing with cyber-attacks in Indonesia is carried out by applying the synergy aspect, namely coordination and communication, which is led by BSSN as the leading sector in the cyber defense sector